2013
DOI: 10.1111/medu.12083
|View full text |Cite
|
Sign up to set email alerts
|

Association of medical student burnout with residency specialty choice

Abstract: Specialty choices regarding lifestyle controllability and income were associated with the amount and type of medical school burnout, as well as with lifestyle-, prestige- and patient care-related motivation. Given that burnout may influence specialty choice, particularly with regard to the primary care specialties, medical schools may consider the utility of burnout prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 40 publications
1
43
0
2
Order By: Relevance
“…Therefore investing in early interventions is the key to minimizing or preventing burnout. Given that medical student burnout is frequent, the interventions should start being implemented in the medical schools, as burnout can even be present prior to the beginning of specialty training and even affect the specialty choice [48, 49]. In our study, we found that one of the important correlates of burnout was home-work demands' interface.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore investing in early interventions is the key to minimizing or preventing burnout. Given that medical student burnout is frequent, the interventions should start being implemented in the medical schools, as burnout can even be present prior to the beginning of specialty training and even affect the specialty choice [48, 49]. In our study, we found that one of the important correlates of burnout was home-work demands' interface.…”
Section: Discussionmentioning
confidence: 67%
“…The problem seems to start at medical school, probably associated with competitiveness, quests for perfection, responsibility and fear of showing vulnerability [18]. In fact, students with higher burnout scores tend to choose specialties with a more controllable lifestyle [36]. Consequences of perfectionism include only short-lived satisfaction with achievements, and a sense that awards are unmerited [20].…”
Section: Key Pointsmentioning
confidence: 99%
“…Recent studies in other countries identified several factors related to the choice and preference, such as gender, career opportunities, prestige, and income [9–11]. Enoch et al demonstrated that specialties that feature a controllable lifestyle (control of work hours) were defined as anesthesiology, dermatology, emergency medicine, neurology, ophthalmology, otolaryngology, pathology, psychiatry, and radiology, while non-controllable lifestyle specialties were surgery, internal medicine, family practice, pediatrics, orthopedic surgery, and obstetrics & gynecology [12]. In the USA, interest in surgery, pediatrics, and obstetrics & gynecology has declined, but the popularity of controllable lifestyle fields such as radiology, psychiatry, dermatology, and ophthalmology has been increasing [13].…”
Section: Introductionmentioning
confidence: 99%